Ser-estar-entre-línguas: um lugar de diferenças para as crianças haitianas se (re)conhecerem - Borsati, Jucélia (2019)
This research is based on the theoretical-analytical device of Discourse Analysis as designed by Michel Pecheux and by some threads in the perspective of Derrida deconstruction. Its corpus consisted of semi-structured interviews applied to nine Haitian immigrant children regularly enrolled at the local school system in Concórdia, a town in the western region of the Brazilian state of Santa Catarina. Here interviews are considered as the very ―self-writing‖, i.e, a singular way of the subject self-utters, tells her/his history, identify her/himself to the language(s), to the other(s), to recognize her/himself. In this perspective, these children are already at/in (the) interlanguages, a space between languages, a place where there is language and there are languages, a discursive area in which there is no possibility of establishing clear limits or defining unambiguous boundaries. According to this approach, there is not any oneness of/in language, not even homogeneity: there are cultural features in language in which the subject is being continuously constituted as the/a language subject. Thus, we start assuming that the immigrant subjects in this research has been constituted in and by this inter-languages space, since when they emigrate they see themselves in another place, they get in contact with another language that is not their own - the inter-languages - as well as with other cultures: the inter-cultures. Our analyses have shown that the immigrant-subject, locating her-himself at the interlanguages as a gap or an intervalar space, sees her/himself in the middle of what appears to be/sounds as weird: the spot, the other(s), the language(s), the culture(s): just everything may cause/produce weirdness on/over her-himself. It could also be noticed that it is hard for the very immigrant-subject to (re)cognize her-himself since when (s)he talks about her-himself, it (re)veals, in a way or another, to be in conflict for being spotted between languages: his-her mother tongue and a/the foreign language. We ourselves did get unease when we realized that the immigrant-subject has generally tried to erase her/his own first language – the mother tongue – in order to (re)mean her/himself in/at another language – the foreign one. In this sense, the inscription of the immigrant-subject into the new language by means of pedagogical practices which allow her-himself to be identified to it may be a suitable way of the subject stands beside the other language – without erasing her/himself and/or her/his own tongue.